Fabrication of milk protein-based electrospun nanofibers - We, Wangyi (Kansas State University, 2022)
The electrospinning technique has been applied to various biopolymers for nanofiber fabrication. In this report, dairy protein-based electrospun nanofibers have been fabricated for its potential application as edible coating material. Whey protein and casein are the two major proteins in milk. It has been known that the electrospinning of dairy proteins (Whey and Casein) is a challenge due to the complex secondary and tertiary structure, and weak internal interactions of dairy proteins. Thus, the first step of the research was about exploration of process parameters during electrospinning of dairy protein. Since the addition Polyvinyl alcohol (PVA) to Whey protein isolate (WPI) solution has an effect on the spinnability, different ratios of WPI and PVA were evaluated. The WPI: PVA mixture and fibers were evaluated in terms of viscosity, conductivity, surface tension, and SEM (scanning electron microscopy) of the nanofiber. In addition, heat denatured whey proteins has been denatured for 2 hours, and the pH of the WPI solution were adjusted to 2 because whey protein exhibits a better spinnability in acid conditions (Vega‐Lugo, 2012). Viscosity and surface tension were increased with the addition of PVA while conductivity was inversely decreased. High concentration of WPI and PVA (6%WPI with 5% and 6% PVA) solutions were not spinnable due to the high viscosity induced rapid solidification at the tip of the syringe. According to the SEM images, fine, beads-free nanofibers were generated with higher PVA concentrations while there were no significant differences among the nanofibers with various WPI concentrations. The effect of PVA on electrospinning of whey protein has been investigated, another dairy protein, casein micelle was also used for fabricating electrospun nanofiber. The effects of MCC (micelle casein concentrate) and PVA (polyvinyl alcohol) blend composition on the spinnability of MCC/PVA solution and the morphology of electrospun nanofiber have been investigated. A blend of MCC and PVA was prepared at different concentrations (MCC: 8, 10, 12, 14% wt, PVA: 0, 1, 2, 3% wt.). As expected, the apparent viscosity of MCC and PVA blends increased significantly (P-value≤0.05) with an increase in MCC and PVA concentration which increased the diameter of nanofiber, while there was only a slight increase in surface tension. The collected nanofibers were characterized using Fourier transform infrared spectroscopy and scanning electron microscopy. From the SEM images, the MCC: PVA blend exhibited nanofiber quality improvement and the ability to form orientationally nonwoven nanofibers which can be collected as edible film. The addition of both MCC and PVA contributes to the spinnability of the blend. However, MCC alone did not possess the effect of increasing spinnability while PVA itself can eliminate the formation of beads. To form fine, smooth, uniformly sized nanofiber, the blend requires at least 2% PVA.
Keywords: Electrospinning; Milk protein based-nanofiber; Edible film